Factors Associated with Early Weaning According to the Report of Mothers in a Child Friendly Hospital Initiative - Teresinha Soares Pereira Lopes (Pesquisa Brasileira em Odontopediatria e Clínica Integrada, 2017)
Objective: To determine the prevalence and factors associated with early weaning according to the report of mothers in a Child Friendly Hospital Initiative. Material and Methods: This is an observational, cross-sectional study with a sample of 252 mother/child binomials, participants in a maternal and childcare program, in a Child Friendly Hospital Initiative in Teresina, Brazil. A semi-structured questionnaire was used as the data collection instrument, administered to the mothers in individual interviews, with questions about socioeconomic conditions, breastfeeding, period, reason and way of weaning; and non-nutritive sucking habits. Early weaning was considered when the supply of breast milk was interrupted before the six months of life. For data analysis, descriptive and bivariate analyses were performed (Pearson's Chi-Square Test and Fisher's Exact Test), with a level of significance of 5%. Results: The prevalence of early weaning was 11.9%. The reasons given for interrupting breastfeeding by the mothers were: 23,% attributions of the mother; 46.% attributions of the infant; 23.3 % organic deficiency of the mother; 6.7% influence of others; and 4.8% of the mothers were still breastfeeding. The finger and/or pacifier sucking habits (p=0.002), and the use of a bottle (p=0.003) were associated with early weaning. A significant association between the total weaning period and the socioeconomic variables was not observed (p>0.05). Conclusion: The prevalence of early weaning was low. The main factors were related to “infant attributions”, associated to children with non-nutritive sucking habits, bottle use, first tooth erupted with less than 6 months and whose mothers had formal employment.